2009
DOI: 10.1038/onc.2009.217
|View full text |Cite
|
Sign up to set email alerts
|

Ect2 links the PKCι–Par6α complex to Rac1 activation and cellular transformation

Abstract: Protein kinase Cι (PKCι) promotes non-small cell lung cancer (NSCLC) by binding to Par6α and activating a Rac1-Pak-Mek1,2-Erk1,2 signaling cascade. The mechanism by which the PKCι-Par6α complex regulates Rac1 is unknown. Here we show that Ect2, a guanine nucleotide exchange factor (GEF) for Rho family GTPases, is coordinately amplified and overexpressed with PKCι in NSCLC tumors. RNAi-mediated knock down of Ect2 inhibits Rac1 activity and blocks transformed growth, invasion and tumorigenicity of NSCLC cells. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
237
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 122 publications
(262 citation statements)
references
References 25 publications
23
237
2
Order By: Relevance
“…ECT2, a proposed oncogene in NSCLC (7), is the other newly discovered binding partner of FXR1. ECT2 is phosphorylated by PRKCI and associated with PAR complex to drive transformed lung cancer cell growth and invasion via activation of ERK signaling cascade (14,25). Here, we provide compelling evidence for ECT2 as a novel mRNA target of FXR1 in lung cancer.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…ECT2, a proposed oncogene in NSCLC (7), is the other newly discovered binding partner of FXR1. ECT2 is phosphorylated by PRKCI and associated with PAR complex to drive transformed lung cancer cell growth and invasion via activation of ERK signaling cascade (14,25). Here, we provide compelling evidence for ECT2 as a novel mRNA target of FXR1 in lung cancer.…”
Section: Discussionmentioning
confidence: 70%
“…More evidence that multiple oncogenic drivers in 3q amplicon cooperate to promote tumorigenesis is indeed emerging. Justilien et al first reported a mechanism by which PRKCI forms a complex with ECT2-PAR6A to drive transformed growth through activation of a RAC1-PAK-MEK1-ERK1,2 signaling axis in NSCLC (14,25). Recently, the same group reported a functional link of PRKCI and SOX2 to activate hedgehog signaling in lung SCC (30 We also demonstrate that although genomic amplification is a key mechanism of FXR1 gene overexpression, it is the gene expression level that drives tumor progression in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In doing so, rounding makes mitosis robust to the environment. Moreover, this may explain the identification of key regulators of mitotic rounding, particularly Ect2 and the ERM family proteins, as oncogenes associated with metastasis and capable of transforming cells to grow in soft agar [28,30]. If these ideas are borne out in experiments, it will be important to reassess the roles of the many other actin cytoskeletal regulators that have been implicated in cancer progression.…”
Section: Resultsmentioning
confidence: 99%
“…Ect2 is up-regulated in a number of cancers including lung, brain, ovarian and bladder [27], and when silenced by RNAi, leads to reduced invasion, tumorigenicity and growth in soft agar in lung cancer cells [28]. Similarly, Ezrin is over-expressed in a huge range of cancer types [29] and has been shown to be essential for metastasis and anchorage independent growth in soft agar [30].…”
Section: Ect2 and Erm Proteins In Mitotic Rounding And Cancer Metastasismentioning
confidence: 99%